Improvement of speed response in four-phase DC–DC converter switching using two shunt voltage-source - A. Yahaya, Jabbar; Mansor, Muhamad; Sulaiman, Suhaila (Institution of Engineering and Technology (IET), 2018)
This study proposes a technique that is able to improve the speed response of a four-phase DC–DC converter switching. The basic concept of the proposed technique is the inclusion of two shunt-connected voltage sources in series to the converter system. Using a higher input voltage to drive the load, a higher current per microsecond output system will be obtained and reverts to its nominal input upon obtaining desired references. Thus, the transient response observed when using this proposed technique is found to be much faster when compared to the conventional converter. Moreover, this technique is easily implemented as it requires only an additional voltage source, power switch, and power diode. The integrated model of the two shunt voltage-source in a four-phase DC–DC converter was simulated in MATLAB/Simulink and validated against the experimental results of a laboratory prototype, 600 W four-phase DC–DC converter. The novelty of this proposed technique is its ability to provide faster operations for critical loads applications, lower output capacitor and lower operating frequency.